AUPS: An Open Source AUthenticated Publish/Subscribe system for the Internet of Things. (December 2016) - Rizzardi, Alessandra; Sicari, Sabrina; Miorandi, Daniele; Coen-Porisini, Alberto
Abstract: The arising of the Internet of Things (IoT) is enabling new service provisioning paradigms, able to leverage heterogeneous devices and communication technologies. Efficient and secure communication mechanisms represent a key enabler for the wider adoption and diffusion of IoT systems. One of the most widely employed protocols in IoT and machine-to-machine communications is the Message Queue Telemetry Transport (MQTT), a lightweight publish/subscribe messaging protocol designed for working with constrained devices. In MQTT messages are assigned to a specific topic to which users can subscribe. MQTT presents limited security support. In this paper we present a secure publish/subscribe system extending MQTT by means of a key management framework and a policy enforcement one. In this way the flow of information in MQTT-powered IoT systems can be flexibly controlled by means of flexible policies. The solution presented is released as open source under Apache v.2 license. Abstract : Highlights: A new secure MQTT mechanism named AUPS(AUthenticated Publish&Subscribe) is defined. AUPS is integrated in a flexible and cross-domain IoT architecture. AUPS is further integrated with a policy enforcement mechanism. AUPS is openly released under Apachev.2 license. A key management system is defined in order to guarantee a good level of security.